A machine learning concept for DTN routing - Dudukovich, Rachel; Hylton, Alan; Papachristou, Christos (IEEE International Conference on Wireless for Space and Extreme Environments conference digest (Online), 2017)
This paper discusses the concept and architecture of a machine learning based router for delay tolerant space networks. The techniques of reinforcement learning and Bayesian learning are used to supplement the routing decisions of the popular Contact Graph Routing algorithm. An introduction to the concepts of Contact Graph Routing, Q-routing and Naïve Bayes classification are given. The development of an architecture for a cross-layer feedback framework for DTN protocols is discussed. Finally, initial simulation setup and results are given.